A Comprehensive Study of Gamma-rays Shielding Features of Binary Compounds - Mahdi Eshghi; M.Reza Alipoor (Progress in Physics of Applied Materials)
In this research, using Geant4 Monte Carlo simulation tool, we have investigated the shielding properties of aluminum oxide, magnesium fluoride, aluminum fluoride, titanium dioxide, magnesium diboride, magnesium silicide, calcium disilicate, and Fluental in the energy range of 0.015 to 10 𝑀𝑒𝑉. In this review, we have calculated and analyzed the linear attenuation coefficient (LAC) and mass attenuation coefficients (MAC), half-value layer (HVL), tenth value layer (TVL), mean free path (MFP), and effective atomic number, effective electron density, equivalent atomic number and buildup factor. In the continuation of the work, we have compared the calculated results of mass attenuation coefficient by Geant4 Monte Carlo simulation tool with the experimental results of others and with the simulation data by XMuDat code, and they have a very low relative error and are in good agreement with each other. Finally, the results obtained for the selected materials are shown in appropriate figures.